1986
DOI: 10.1111/j.1529-8817.1986.tb00035.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF CURRENT VELOCITY AND LIGHT ENERGY ON THE STRUCTURE FO PERIPHYTON ASSEMBLAGE IN LABORATORY STREAMS1

Abstract: Effects of current velocity and light energy on the taxonomica and physiognomic characteristics of periphyton assemblages were investigated in laboratory streams. The initial rate of colonization was related to current velocity, while the effects of light energy accounted for differences in species composition by the end of the experiment. Although the laboratory systems had many species in common during the realy stages of colonization, the experimental treatments generated differences in rates of communityde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
84
1
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(91 citation statements)
references
References 27 publications
3
84
1
3
Order By: Relevance
“…Many factors interact for controlling development of algal periphytic communities such as nutrient availability, light, flow velocity, pH, temperature, grazing, which can affect abundance, production and community structure (Fairchild et al 1985, Steinman & McIntire 1986, Keithan et al 1988, Bothwell 1988, Peterson et al 1993, Rosemond et al 1993, Pan & Lowe 1994, Pringle & Hamazaki 1997, Rosemond et al 2000. Several experiments of N and P enrichment suggest that nitrogen availability can constitute an essential element in the regulation of primary benthic production (Lohman et al 1991, Perrin & Richardson 1997.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors interact for controlling development of algal periphytic communities such as nutrient availability, light, flow velocity, pH, temperature, grazing, which can affect abundance, production and community structure (Fairchild et al 1985, Steinman & McIntire 1986, Keithan et al 1988, Bothwell 1988, Peterson et al 1993, Rosemond et al 1993, Pan & Lowe 1994, Pringle & Hamazaki 1997, Rosemond et al 2000. Several experiments of N and P enrichment suggest that nitrogen availability can constitute an essential element in the regulation of primary benthic production (Lohman et al 1991, Perrin & Richardson 1997.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, high light exposure causes the formation of complex biofilms with multiple layers and enhances the competitive advantage of the MG in nutrient consumption . Diatom communities also change with geology and river typology (Rimet, 2009;Tison et al, 2005), current velocity (Steinman and McIntire, 1986), predation (Feminella and Hawkins, 1995;Steinman, 1996), depth (Cantonati et al, 2009), type of substrate (Cazaubon et al, 1995;Eminson and Moss, 1980;Torrisi et al, 2006), hydrology (Falasco et al, 2016) and according to the presence of humic substances or metals (Morin et al, 2008). The high profile guild, by virtue of its position in contact with the water column, is probably the ecological guild under the influence of the greatest number of factors, including light , current intensity (Passy, 2007;Stenger-Kovács et al, 2013), predation (Steinman, 1996 and exposure to herbicides (Larras et al, 2014;Marcel et al, 2013;Rimet and Bouchez, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, the organisms that inhabit in running waters need mechanisms to avoid or resist mechanical stress caused by water flow (Gordon et al 1992). Thus, several authors have suggested that the disturbance produced by current velocity is very important to the settlement and maintenance of the periphytic biomass in lotic ecosystems (Horner & Welch 1981, Steinman & McIntire 1986, Lamberti et al 1991, Uehlinger et al 1996.…”
Section: Introductionmentioning
confidence: 99%